CONDITION OF THE UTERINE CERVIX DURING UNCOMPLICATED MULTIPLE PREGNANCY - Sukharev, A. B.; Kopitsa, T. V. (Eastern Ukrainian Medical Journal, 2019)
Premature birth is an actual problem of modern obstetrics. There is a lot of different reasons for preterm delivery. It includes maternal and fetal complications and forms one major obstetric syndrome. One of the anatomical components of it is the cervix. Objective of the study was to examine the state of the cervix during a normal multiple pregnancy. In addition, our task was to find a progressive decrease in the length of the cervix with increasing gestational age. Starting from 22-24 weeks, the rate of cervical shortening in pregnancy with twins is much higher than those in singleton pregnancies. However, the most pronounced difference in the length of the cervix in multiple pregnancies and single pregnancies was observed in the third trimester of pregnancy. Previous studies have indicated that at the time of birth, the length of the cervix in patients with multiple fetuses was significantly shorter than in singleton pregnancies. In most patients, the internal os was Y-shaped. The study was carried out in the city clinical maternity hospital during 2013–2017. The data were collected from 20 pregnant women (group I) with dichorial twins, who had pregnancy without complications and ended in term delivery. In the second group we united 20 pregnant women with a singleton pregnancy without any complications. The data were collected from using clinical examination methods, generally accepted laboratory tests. Transvaginal cervicometry was performed to understand the threat of preterm delivery. We used a modern ultrasound device “Mylab Seven” with a 6.5 MHz. The study showed that for multiple pregnancies, as well as for singleton pregnancies, patients who have given birth on time are characterized by a progressive decrease in the length of the cervix as the duration of pregnancy increases. Based on the finding, starting from 22–24 weeks of gestation, the rate of cervical shortening is significantly higher than that in singleton pregnancies. The study proved that the most pronounced difference in the length of the cervix in multiple pregnancies and single pregnancies is observed in the third trimester of pregnancy.